Negotiating Gender Justice between State, Religion, and NGOs: A Lebanese Case - Grung, Anne Hege (Religions, 2018)
This article explores part of the process of passing a law in the Lebanese Parliament on 1 April 2014 called Law on the protection of women and other members of the family from domestic violence, also known as the Protection Law' or Law 293. In a United Nations Research Institute for Social Development (UNRISD) project on Religion, Politics and Gender Equality, the theorists José Casanova and Anne Phillips are engaged in establishing a transnational perspective on religious gender politics. The article then draws on written documentation regarding the discourse connected to the draft law at that time and on field interviews. The interviews were conducted in the period 2013-2016 with religious leaders and resource persons in Christian, Sunni, and Shi'a communities in Lebanon, and with key persons in the NGOs KAFA and ABAAD. An analysis of the arguments for and against the law before it was passed displays the larger field of intersection between feminism and religious practices and the consequences of the Lebanese dual court system. As a study from the Lebanese context when Law 293 was being intensively discussed, the article shows both the authority and the vulnerability of the religious leaders associated with the dual court system. The article also reveals the ambiguity of feminist activists and NGOs toward the role of the religious communities and leaders in Lebanon.